Fabrication of a thin silicon detector with excellent thickness uniformity - Valtonen E; Eronen T; Nenonen S; Andersson H; Miikkulainen K; Eranen S; Ronkainen H; Makinen J; Husu H; Lassila A; Punkkinen R; Hirvonen M (Elsevier Science BV, 2022)
We have fabricated and tested a thin silicon detector with the specific goal of having a very good thickness uniformity. SOI technology was used in the detector fabrication. The detector was designed to be used as a Delta E detector in a silicon telescope for measuring solar energetic particles in space. The detector thickness was specified to be 20 mu m with an rms thickness uniformity of +/- 0.5%. The active area consists of three separate elements, a round centre area and two surrounding annular segments. A new method was developed for measuring the thickness uniformity based on a modified Fizeau interferometer. The thickness uniformity specification was well met with the measured rms thickness variation of 43 nm. The detector was electrically characterized by measuring the I-V and C-V curves and the performance was verified using a Am-241 alpha source. (C) 2015 Elsevier B.V. All rights reserved.